Training Future Software Developers to Acquire Agile Development Skills. - Chuan-Hoo Tan; Hock-Hai Teo (Communications of the ACM, 2007)
The article discusses the authors' experience with undergraduate software development projects completed by students using agile development skills. Agile techniques include a high emphasis on group collaboration, utilization of individual team member strengths, functional modularity, short iteration cycles, and an avoidance of "overdeveloped" modules. The authors observed that students performed better using agile techniques. They also noted several improvements they could add to the learning process, including the use of a multitiered software platform, and the introduction of skills in conflict resolution.